Dialectical text and show in the theater "Concepts of theory" - بصل , محمد; يوسف , أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research discusses theatrical text and show and between them , trying to explain their concept and nature of each . Because the written text is a document the play from loss, It is the basis for every theatrical show . Also a theatrical text cannot survive without being embodied in a visual and audible show on stage, as for a group of spectators who came to judfe it success or failure . The research was divided into four sections : the theatrical text, its concept and nature, the theatrical show, its concept and nature, text and show priority, and the binary text of the writer and the director,s text . The study according to the semiotic theory .